A Dual TLR7/TLR9 Inhibitor HJ901 Inhibits ABC-DLBCL Expressing the MyD88 L265P Mutation - An, Beiying; Zhu, Shan; Li, Tete; Wu, Jing; Zang, Guoxia; Lv, Xinping; Qiao, Yuan; Huang, Jing; Shao, Yan; Cui, Jiuwei; Liu, Yong-Jun; Chen, Jingtao (Frontiers in Cell and Developmental Biology, 2020)
The activated B-cell-like (ABC) subtype is a diffuse large B-cell lymphoma (DLBCL) and is associated with aggressive clinical cases and poor prognosis despite recent advances in disease treatment. In ABC-DLBCL, the most severe damaged signaling pathways converge to aberrantly activate the toll-like receptor (TLR) 7/9/MyD88 pathways, leading to the avoidance of cell death and resistance to chemotherapy. Gain of function mutation in MyD88 (MyD88 L265P) enhanced nuclear factor kB (NF-kB) and Janus kinase/signal transducer and activator of transcription (JAK-STAT) signaling pathways, associated dysregulation of TLR signaling in pathogenesis of ABC-DLBCL. Therefore, Inhibition of the TLR signaling network might be essential for increasing the improvement of clinical outcomes. In this study, we designed a de novo synthesized oligodeoxynucleotide-based antagonist of TLR7 and TLR9, referred to as HJ901, which competitively binds to TLR7/9. We profiled HJ901 inhibition in various DLBCL cell lines, as well as verified tumor suppression in a xenograft mouse model. We found that HJ901 treatment significantly reduced TLR7- and TLR9-mediated cell proliferation and cytokine production in a time- and dose-dependent manner in a variety of DLBCL cell lines expressing the MyD88 L265P mutation. Moreover, HJ901prevented tumor growth and down regulated NF-κB and JAK2-STAT3 signaling pathways in a DLBCL xenograft mouse model with the MyD88 L265P mutation. These results elucidate the anti-tumor effect of a synthesized oligodeoxynucleotide-based antagonist, HJ901, which competitively binds to TLR7/9, may be associated with the down-regulation of NF-κB and -JAK2-STAT3 signaling pathway, and may provide a rationale for treatment of ABC-DLBCL patients that have the MyD88 L265P mutation.